Penulisan Arab Melayu Dengan Metode Imla’ di Madrasah Diniyah Takmiliyah Awaliyah - Abdi Sampurna Nasution; Ahmadi Ilal Khoir; Muhammad Arrival Dzaky; Muhammad Nur Fajri; Sahkholid Nasution (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research aims to find out Malay Arabic writing using the Imlak method at MDTA, to study the problems of students in studying Malay Arabic, collecting data through interviews, documentation and observations, the name of the school is Madarsah Diniyah Takmiliyah Awaliyah Arridho, on December 15 2023 , the data source was obtained by two interviewers who interviewed 2 people (Dian Biological and Novi Angelia), a total of 10 teachers, and a total of 156 students, located on Jalan Platina Raya Environmental 21, Medan Marelan District, Kota Madya. The results of this research explain that there are Some of the problems with Malay Arabic writing at MDTA, these factors are caused by differences in background, students' lack of seriousness in understanding, lack of explanation from teachers so that students find it difficult to understand, little sense of sincerity in learning, lack of motivation, learning places that are not conducive, and few teachers can influence students that learning is very useful. The solution given by teachers is that each teacher must embody their respective roles, not violate the teacher's code of ethics, not take out the frustration they have faced on students, be friendly towards students, not only prioritize smart students, and have thorough preparation.